Alginate films as carriers of probiotic bacteria and Pickering emulsion - Medeiros, Jackson Andson [UNESP]; Otoni, Caio Gomide; Niro, Carolina Madazio; Sivieri, Katia [UNESP]; Barud, Hernane S.; Guimarães, Francisco E.G.; Alonso, Jovan D. [UNESP]; Azeredo, Henriette M.C. (Elsevier, 2022)
Bioactive edible films have been proposed from a calcium-crosslinked alginate matrix added with probiotic bacteria (Bacillus coagulans, as the bioactive component) and/or bacterial cellulose nanocrystal (BCNC)-stabilized palm olein Pickering emulsion (as a hydrophobizing component). The emulsion, however, instead of increasing the surface hydrophobicity and the barrier to water vapor, decreased both, due to discontinuities on the film structure and possibly the BCNC layer around the droplets minimizing the surface exposure of the hydrophobic phase (and its effects on film hydrophobicity). The probiotic bacteria, on the other hand, besides increasing the elastic modulus (which was ascribed to electrostatic interactions between teichoic acid and calcium), also enhanced both surface hydrophobicity and barrier to water vapor, probably due to the hydrophobicity of Bacillus spores. The probiotics exhibited high viability (> 8 log cfu.g−1, on a dry film basis) during film drying, storage, and digestion in a simulated gastrointestinal tract.
Keywords: Functional foods; Polysaccharides; Tensile properties; Water vapor permeability